2014
DOI: 10.1002/lpor.201300142
|View full text |Cite
|
Sign up to set email alerts
|

An ultra‐black silicon absorber

Abstract: An ultra-black (A > 99%) broadband absorber concept on the basis of a needle-like silicon nanostructure called Black Silicon is proposed. The absorber comprises Black Silicon established by inductively coupled plasma reactive ion etching (ICP-RIE) on a highly doped, degenerated silicon substrate. Improved absorbers also incorporate an additional oxide capping layer on the nanostructures and reach an absorptance of A > 99.5% in the range of 350 to 2000 nm and A ∼ 99.8% between 1000 and 1250 nm. Fabrication of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 32 publications
(45 reference statements)
3
46
0
1
Order By: Relevance
“…11,17,19,[43][44][45][46] In addition, also pure optical applications like silicon lenses or windows for the IR and light absorbers 47 can greatly benefit from the exceptionally good antireflection effect induced by the needle-like Black Silicon nanostructure. Among the multitude of fabrication methods for Black Silicon, ICP-RIE seems to be the most reasonable choice for most of the named applications because of its very good repeatability and reliability, the excellent chemical and structural intactness of the produced structures, 20,48 and its applicability to all forms of silicon, irrespective of the degree of structural order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17,19,[43][44][45][46] In addition, also pure optical applications like silicon lenses or windows for the IR and light absorbers 47 can greatly benefit from the exceptionally good antireflection effect induced by the needle-like Black Silicon nanostructure. Among the multitude of fabrication methods for Black Silicon, ICP-RIE seems to be the most reasonable choice for most of the named applications because of its very good repeatability and reliability, the excellent chemical and structural intactness of the produced structures, 20,48 and its applicability to all forms of silicon, irrespective of the degree of structural order.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the thin (about 30 nm) conformal Al 2 O 3 layers can even further reduce the already very low Black Silicon surface reflection in the UV region. 47 It should be noted that good surface passivation by thin, thermally grown SiO 2 is reported in the literature, too. 44 Altogether, it can be concluded that sufficient surface passivation of Black Silicon nanostructures by ICP-RIE is technologically feasible nowadays.…”
Section: -9mentioning
confidence: 96%
“…In both cases the front side reflection is suppressed to about 3% and the forward scattering of the incident light leads to a strongly increased absorptance in the NIR. It should be noted that even lower broadband reflectances below 0.5% (already including a dielectric passivation layer) are feasible with deeper b-Si structures [11]. Moreover, the polycrystalline CSG film benefits strongly from application of b-Si and shows an overall absorptance gain of 70% in the PV relevant range between 300 and 1100 nm [12].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Vertically aligned carbon nanotube (VACNT) black [8,[10][11][12][13], black Si [1,4,14,15], gold black [16], and laser-ablated metal surfaces [2,17] exhibit low reflectance around or below 1% in the visible to near infrared (mid or far infrared in some cases) range of wavelengths.…”
Section: Introductionmentioning
confidence: 99%